Sri Lankan intellectual capital disclosure: An empirical analysis - Pratheepkanth Puwanenthiren; Alagathurai Aj anthan; Lingesiya Kengatharan (Universitas Trisakti, 2019)
This study examines voluntary IC disclosure provided by Sri Lankan firms in annual reports from the year 2016/17. A 100-firms sample, from the Colombo stock exchange (CSE)-listed firms. Findings suggest that Sri Lankan firms, on average, are aware of the significance of IC disclosure. Concerning the descriptive analysis, the results indicate that most of the information reported (41 percent) is related to human capital; 31 percent is related to relational capital and the 21 percent concerns structural capital disclosure. The results also suggest that industry nature and firm size play a key role as a determinant for the disclosure of IC in Sri Lankan annual reports. As the no definite IC disclosure framework has been established within Sri Lankan firms. Concurrently as Sri Lanka passes through its post-war-recovery phase, reform of its mutually agreed financial reporting framework is essential to reduces information asymmetry and therefore reducing the agency costs.